If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5 + 12 = 17x + -3 + -16x Combine like terms: -5 + 12 = 7 7 = 17x + -3 + -16x Reorder the terms: 7 = -3 + 17x + -16x Combine like terms: 17x + -16x = 1x 7 = -3 + 1x Solving 7 = -3 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 7 + -1x = -3 + 1x + -1x Combine like terms: 1x + -1x = 0 7 + -1x = -3 + 0 7 + -1x = -3 Add '-7' to each side of the equation. 7 + -7 + -1x = -3 + -7 Combine like terms: 7 + -7 = 0 0 + -1x = -3 + -7 -1x = -3 + -7 Combine like terms: -3 + -7 = -10 -1x = -10 Divide each side by '-1'. x = 10 Simplifying x = 10
| -5x*-3+8= | | 7x+1=-20 | | -5x*3+8= | | -3(x+8)-43=2-42 | | solvex^2=-7x-7 | | 22-x=2x+10 | | 22-x=2(x-5) | | -4-7=-9+x | | -3(x-4)=18 | | 2(5c-1)-1=6c+9 | | 8x+7-5x=-17 | | 6-6(18x-12)=4x | | x^2+25x-150=0 | | 4(2x-4)=9x | | (x-2)-(2-x)= | | 10-5= | | 40+3y-12=13y-14-3y | | -(3y-5)+11= | | (6m-1)2=10 | | 70-2(x+3)=3(x-2) | | 5=9y | | 12(2x-6)+37=3x | | -6(4d+8)= | | 12x-(3x-12)=5+8x | | 2x^3+54= | | -3(6n-4)+3n= | | (x-1.4)=36 | | 36(x-1.4)= | | 20m^2+43m+14= | | 11-45=5(x-3)-4 | | 17(5c-1)-14=83c+17 | | -19n+12=-15n-12 |